Sicardicoris, a new Madagascan subgenus of Peyrierocoris Chłond & Junkiert 2010 (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) - Chłond, Dominik; Guilbert, Eric (Zootaxa, 2012)
Sicardicoris, a new subgenus of Peyrierocoris Chłond & Junkiert and one new species Peyrierocoris (Sicardicoris) nigeris described on the basis of specimens selected from the collection of the Muséum national D’Histoire naturelle, Paris.Description with drawings of dorsal habitus and characters of male and female genitalia are given. A key to all the species of the genus is also provided.